Sustainable Food Consumption and Principles of Justice in Italy - Tronca, Luigi; Capitello, Roberta (Social justice research, 2025)
Public awareness of the environmental impacts of food systems and their implications for people’s lives is growing in many countries. There is also an increasing recognition of the links between sustainability and social justice goals. The objective of this study was to examine the relationship between perceptions of social justice and sustainable consumption in the context of food. The study employed Rawls’s theory of social justice and was based on a survey conducted in Italy with a representative sample of 2000 respondents. The analysis encompassed indicators of sustainable consumption, political orientation, and attitude toward a sustainable lifestyle. The findings confirmed that in Italy, the sense of social justice is mainly inspired by the maximin principle, which drives toward sustainability depending on political orientation and the motivation for lifestyle change. The principle of egalitarianism seems to be the least effective in concretely supporting sustainable consumption, whereas utilitarianism has the potential to facilitate sustainability-related practices when based on personal motivations. This study contributes to advancing knowledge on the relationship between sustainable food consumption and the sense of social justice, which is a crucial condition for societal contexts that support the idea of affordable, sustainable options for all consumers.